Effect of Constitutional Rights on Labour Law in some Countries and Vietnam - Le Thu, Nguyen (VNU Journal of Science: Legal Studies, 2024)
As the core legal document of each country, the Constitution is the founding document for the establishment and development of all regulations regulating society. As a result, the effect of constitutional rights on relations between private actors is one of the pressing issues to be researched. In accordance with this research orientation, this article focuses on identifying, evaluating and analyzing some legal issues on the effect of constitutional rights in the field of labour law. The research is taken from the assessment of some legal systems around the world and Vietnam, which in turn is the base for proposing some prospective research on the effect of constitutional rights in the field of labour law in Vietnam.